Standard Budget Value in the Maintenance of Automated Weather Observing System (AWOS) Equipment at the Meteorology, Climatology and Geophysics Agency - Arum Indri R; Arifiani Widjayanti; Ridwan Rajab (International Journal of Economics Development Research (IJEDR), 2023)
This research addresses the inefficiencies in proposing maintenance budgets for optimizing the utilization of Automated Weather Observing System (AWOS) spare parts. The primary objective is to analyze the calculation methodology for establishing an ideal standard budget for AWOS maintenance, considering various influencing factors. Employing an applied research method with a qualitative approach, data for the study are derived from interviews and literature studies. The findings reveal that several factors impact the standard budget, encompassing the number of technicians, duration of maintenance, geographical location, transportation, accommodation, daily allowances, type of damage, and the nature of maintenance (preventive/corrective). The standard budget calculation is grounded in maintenance service costs, official travel expenditures, and spare parts procurement costs. Service fees for third-party maintenance are determined through collaborative contracts, while official travel costs align with predetermined standard input expenses. Replacement costs for spare parts are based on UPT reports, expert recommendations, historical maintenance records, priority scaling, and budgetary constraints. The ongoing development of a spare parts analysis method, factoring in these considerations, indicates that the optimal procurement for data logger spare parts is 8 units, with a 90% confidence level for all of Indonesia. This approach aims to ensure AWOS functionality aligns with its technical life (reliability), ease of repair in the event of failure (maintainability), and consistent proper operation (availability).